UJI AKTIVITAS ANTIBAKTERI SENYAWA 4 DIMETILAMINOKALKON TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI ATCC - WIWIT SEPVIANTI (Universitas Pahlawan Tuanku Tambusai, 2021)
Introduction: Pathogenic bacteria infection are the main cause of human disease, for example diphtheria, pneumonia, cholera, tuberculosis, dysentery and typhus. Giving antibiotics is the treatment for infectious diseases caused by bacteria, but the treatment of these infections became more difficult because of the drug resistant strains. This is what drives the development of new antibiotic compounds. Chalcone is one of the potential candidates as an antibacterial. Objective: Testing Antibacterial acitivy of 4-dimethylchalcone against Staphylococcus aureus and Escherichia coli ATCC bacteria. Methods: In this study, an antibacterial activity of 4-dimethylaminocahlcone was test at The methods that used to evaluate antibacteria activity of chalcone is agar diffusion. The variation of the chalcone concentration used was 0.625; 1.25; 2.5 and 5%. Results: The 4-dimethylaminocalcone compound showed moderate antibacterial activity against gram-negative bacteria (Escherichia coli ATCC) with the highest inhibitory zone diameter of 8 mm and and percentage of inhibition ability of 61.54%. at a concentration of 5% while in gram-positive bacteria (Staphylococcus aureus ATCC) was weak with a inhibitory zone diameter of only 0.7 mm and percentage of inhibition ability was only 3.89%. Conclusion: Antibacterial tests of 4-dimethylaminocahlcone showed that chalcone increased the antibacterial activity at Escherichia coli ATCC bacteria but decreased Staphylococcus aureus ATCC bacteria. Keyword: antibacterial, chalcone, Escherichia coli , Staphylococcus aureus